El estudio de diseño en la promoción de la ciudadanía: un proyecto educativo desarrollado en Aoteaora - Mortensen Steagall, M; Tavares, T (Universitat de Vic - Bau, Centre Universitari de Disseny (https://www.baued.es/ca), 2021)
This study describes the framework of a brief developed for level 7 of a Bachelor of Graphic Design major in Communication Design and the design outcomes developed during an academic semester in Aotearoa. The brief employed the Design Studio approach to integrating social, technical and cognitive dimensions of knowledge construction. We explored the potential of Social Design to engage students in real-world problem and design outcomes to improve local and global contexts, facing problems that are complex and have long-term effects. The study sits in the post-positivist paradigm, and prioritizes the pluralism between quantitative data, and the qualitative perspectives of historical, comparative, philosophical, and phenomenological analysis. It contributes to discussions about the design studio approach in Design Education and methodologies for the development of tertiary-level curricula.
Keywords: Design Education; Social Design; Design Studio; Design Atelier; Design-based research